A process of leaching recovery for cobalt and lithium from spent lithium-ion batteries by citric acid and salicylic acid. Issue 44 (16th August 2021) - Xu, Meiling; Kang, Shumei; Jiang, Feng; Yan, Xinyong; Zhu, Zhongbo; Zhao, Qingping; Teng, Yingxue; Wang, Yu
Abstract : A new mixed organic acid of citric acid and salicylic acid is proposed to recover valuable Co and Li ions from spent LIBs. Under the optimum leaching conditions, the leaching efficiencies of Co and Li ions can reach 99.5% and 97%. Abstract : There is great economic and environmental value in recovering valuable metal ions from spent lithium-ion batteries (LIBs). A novel method that employs organic acid recovery using citric acid and salicylic acid was used to enhance the leaching of metal ions from the cathode materials of spent LIBs. The effects of the acid concentration, reducing agent content, solid to liquid (S : L) ratio, temperature, and leaching time were systematically analyzed and the optimal acid leaching process condition was determined through the results. The kinetics of the leaching process with different temperatures was analyzed to explore and verify the relationship between the leaching mechanism and temperature. The results of TG/DSC analysis showed that the optimum calcination temperature was 500 °C for 1 h and 600 °C for 3 h. The XRD and micromorphology analysis results showed that cathode material powders without impurities were obtained after pretreatment. The experimental results demonstrated that the optimal leaching efficiencies of the metals ions were 99.5% Co and 97% Li and the optimal corresponding condition was 1.5 M citric acid, 0.2 M salicylic acid, a 15 g L −1 S : L ratio, 6 vol% H2 O2, 90 °C, and 90 min. Afterward, the infrared tests and SEM morphologies results indicated that only salicylic acid was present in the residue after filtration because of the microsolubility of the salicylic acid. Finally, it was obvious that the temperature had a great influence on the leaching process as observed through the kinetics and thermodynamics analyses, while the E a values for Co and Li were obtained as 37.96 kJ mol −1 and 25.82 kJ mol −1 through the kinetics model. The whole process was found to be efficient and reasonable for recovering valuable metals from the industrial electrodes of spent LIBs.